WHAT DRIVES SHOPEEFOOD PURCHASES? EXPLORING THE ROLE OF SERVICE QUALITY, PROMOTION, PRICE, AND BRAND IMAGE IN SAMARINDA CITY - Umi Zunaidah; Devina Vionita; Renita Kawuryan; Armini Ningsih; Rusliansyah (RADJA PUBLIKA, 2025)
ShopeeFood is an integrated service within the Shopee application, offers online food and beverage delivery. This study aims to analyze and provide empirical evidence on the impact of service quality, promotion, price, and brand image on consumers' purchasing decisions on ShopeeFood. Utilizing a quantitative research design, the sample was selected through purposive sampling, consisting of 100 respondents who are active ShopeeFood users in Samarinda City. Data was gathered using an online questionnaire distributed via Google Forms. The research employs several data analysis techniques, including validity and reliability tests, classical assumption tests (such as normality tests), and multiple linear regression analysis. Hypothesis testing was conducted through partial tests, simultaneous tests, and coefficient determination tests. The analysis was performed using SPSS version 26, with responses measured on a Likert scale ranging from 1 to 5. The findings reveal that service quality, price, and brand image significantly influence purchasing decisions, whereas promotion does not have a significant impact. The study provides valuable insights into the factors influencing consumer choices on ShopeeFood in Samarinda City.